2021
DOI: 10.48550/arxiv.2107.02975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Natural Language Processing for Unstructured Data in Electronic Health Records: a Review

Abstract: Electronic health records (EHRs), digital collections of patient healthcare events and observations, are ubiquitous in medicine and critical to healthcare delivery, operations, and research. Despite this central role, EHRs are notoriously difficult to process automatically. Well over half of the information stored within EHRs is in the form of unstructured text (e.g. provider notes, operation reports) and remains largely untapped for secondary use. Recently, however, newer neural network and deep learning appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 193 publications
(248 reference statements)
0
6
0
Order By: Relevance
“…NLP models are increasingly implemented on medical health care records for information extraction, representation learning and phenotyping 33 . We have compared multiple approaches, including state of the art T5 and Google BERT transformer models, in which Google PubMedBERT showed the highest model performance.…”
Section: Discussionmentioning
confidence: 99%
“…NLP models are increasingly implemented on medical health care records for information extraction, representation learning and phenotyping 33 . We have compared multiple approaches, including state of the art T5 and Google BERT transformer models, in which Google PubMedBERT showed the highest model performance.…”
Section: Discussionmentioning
confidence: 99%
“…authors have reviewed the possibility of automating a number of tasks including disease diagnoses, disease prediction, phenotype modelling, disease classification, and developing training representations of medical concepts, such as diseases and medications. Li et al [8] focused on a broad scope of tasks, such as classification and prediction, word embedding, extraction, generation, and similar matters such as question answering, phenotyping, generating knowledge graphs, forming medical dialogue, and supporting multilingual communication and interpretability. They reviewed multiple recent studies that showed how such tasks could be supported by electronic health records and health informatics, concluding that Deep learning methods in the general field of NLP have achieved remarkable success, but that applying them to the field of biomedicine remains challenging due to limited data availability and additional difficulties associated with domain-specific text data.…”
Section: Related Workmentioning
confidence: 99%
“…According to van der Lee et al [32], there are three families of datato-text generation methods: statistical machine translation [16,20,28,31], neural machine translation [5,8,15,17,19,24,25,30,40], and rule-based linguistic summarization [2,10,27]. Neural and statistical methods generally involve training models to automatically generate natural language summaries of data, while rule-based methods depend on the use of protoforms to model their summary output.…”
Section: Related Workmentioning
confidence: 99%